COGNITIVE LIMITATIONS OF R&D-ENGINEERS IN THE PRODUCT CREATION - Gobert, Michael (Doprava a spoje, 2012)
The Product Development as well as the surrounding Product Creation is characterised by a high uncertainty. Although a basic requirement list specifies the task, the conversion to a final layout of the product demands a lot of information processing and many decisions. The Engineering Design Methodology supports the R&D Engineering during this task. According to a structured list, he is guided through the different steps and the corresponding decisions of the engineering design process. In this occasion, R&D Engineers use strategies of processing and simplification due to cognitive restrictions. The inappropriate use of them may lead to biases. Based on the Planning and Design Process, the main cognitive limitations of R&D Engineers are examined in this article.